The Effect of E-Commerce, Digital Marketing, and Sharia-Based Business Management on Micro, Small, and Medium Enterprises (MSMEs) Revenue in Wonogiri Regency - Annisa Nur Rohmah; Devina Melinawati; Indra Setiawan (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
Micro, Small, and Medium Enterprises (MSMEs) face challenges in increasing revenue and adhering to Islamic business ethics in the digital era. This study aims to analyze the effect of Sharia-based E-Commerce, Digital Marketing, and Business Management on MSMEs revenue in Wonogiri Regency. This quantitative associative research involved MSME actors in Selogiri and Wonogiri sub-districts selected through non-probability sampling. Data were collected via questionnaires and analyzed using multiple linear regression analysis. The results show that simultaneously, E-Commerce, Digital Marketing, and Business Management significantly affect MSME revenue. Partially, Sharia-based Business Management has the most dominant positive effect, followed by Digital Marketing. Interestingly, E-Commerce does not have a significant partial effect on revenue. This finding indicates that e-commerce platforms act merely as supporting facilities (enablers), while effective business management—rooted in Islamic principles such as honesty and trust—and active digital marketing strategies serve as the primary drivers for increasing revenue. Therefore, MSMEs should prioritize improving managerial capacities and marketing strategies rather than merely relying on digital platform existence to enhance their financial performance.